Particle swarm optimization of micro air launch vehicle trajectory - Omar, Hanafy; Idres, Moumen; Kafafy, Raed (Canadian Aeronautics and Space Institute, 2011)
The demand for sub microsatellites is growing rapidly. A new low-cost launching method is needed to launch these types of satellites. This can be done by launching from airplanes. By implementing air launching, there would be no restrictions on the launch site, the launch angle, and the launch direction. In this paper, trajectory optimization of the micro air-launch vehicle (MALV) is carried out using the particle swarm optimization method. The problem is treated as a parameter optimization problem, and it is formulated as a single objective constraint optimization problem with the explicit objective of maximizing the payload mass. The simulation results show the effectiveness of the proposed technique in solving the nonlinear optimal trajectory problem for MALV